(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2018)
Pietro Calà Ulloa (1801-1879), Prosecutor of the Criminal Court of Trapani, is known by scholars for a report written in 1838. This work is considered one of the first document addressing mafia issue. Specifically he focused on behaviours which can be related to mafia phenomenon. In his report the Prosecutor, loyal to the Bourbon kingdom, grasped interesting aspects of the Sicilian reality, but fearing a “political upheavel”, he kept together opponents and criminals. Keywords: parties, cults, factions, pre-mafia phenomena, mafia